2002
DOI: 10.1155/s1110724302000372
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Ensheathing Glia: Drivers of Axonal Regeneration in the Central Nervous System?

Abstract: Olfactory ensheathing glia (OEG) accompany olfactory growing axons in their entry to the adult mammalian central nervous system (CNS). Due to this special characteristic, considerable attention has been focused on the possibility of using OEG for CNS regeneration. OEG present a large heterogeneity in culture with respect to their cellular morphology and expressed molecules. The specific characteristics of OEG responsible for their regenerative properties have to be defined. These properties probably result fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 44 publications
1
56
0
Order By: Relevance
“…and West, 2002;Moreno-Flores et al, 2002;Chung et al, 2004). Our functional genomic study supports this hypothesis and goes one step further, for the first time identifying candidate genes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…and West, 2002;Moreno-Flores et al, 2002;Chung et al, 2004). Our functional genomic study supports this hypothesis and goes one step further, for the first time identifying candidate genes.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, it is thought that OECs are important in permitting the continuous growth and synaptogenesis of olfactory receptor axons in the CNS (Doucette, 1990). In the light of this, OECs have become one of the main candidates for cell transplantation in rodent models of spinal cord injury (Moreno-Flores et al, 2002;. Indeed, their axon outgrowthpromoting properties have been analyzed in in vitro and in vivo models of axonal CNS injury (Chuah and West, 2002;MorenoFlores et al, 2002;Wewetzer et al, 2002;Boyd et al, 2003;Barnett and Chang, 2004;Raisman, 2004;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also have the advantage of being able to migrate into the surrounding tissues. [61][62][63][64] ESC have also been shown to have the ability to differentiate into oligodendrocytes and myelinate naked axons in culture. The outcome in animal models of SCI is improved by the use of suitable polymer scaffolds within the lesion site designed to provide a framework for the regenerating axons.…”
Section: Stem Cell Experiments On Animal Models Of Neurological Diseasementioning
confidence: 99%
“…A variety of purification methods have been implemented, including the sorting of cells based on their expression of different molecules, such as sulfatide O4, and not expressing others, like galactocerebroside 20 , immunopurification techniques, selection of positive cells for different receptors, and methods based on differential adhesion of OECs. It was demonstrated that OECs are very heterogeneous regarding their morphology and markers expressed in culture, also after purification 21,22,23 .…”
Section: Characteristics Of Olfactory Ensheating Cellsmentioning
confidence: 99%